Estudo retrospectivo longitudinal sobre produção e composição do leite na mesorregião noroeste rio-grandense - Sicheski, Sirineu José (2018)
The production of foods of animal origin such as meat, milk, and their derivatives must be intensified on a global scale in a sustainable way. Here, our objective was to evaluate milk production, chemical composition (total dry extract, defatted dry extract, fat, protein, and lactose), somatic cell count, and total bacterial count, in relation to season (summer, fall, winter, and spring) on a rural property in the municipality of Palmeira das Missões, Rio Grande do Sul, Brazil between January 2009 and December 2016. This case study was delineated as a longitudinal retrospective. The main variable analyzed was the production of milk per hectare per month, as this is paramount in the evaluation of a rural property. The consecutive longitudinal retrospective study over the course of 8 years serves to emphasize that the organized execution of the activities related to animal husbandry and milk production reduces the coefficients of variation referring to the composition of the milk. In other words, it is easier to maintain milk quality, in addition to the generation of extra revenue by way of a bonus milk quality. The normative instructions from Nos. 51 and 62 of the Ministério da Agricultura, Pecuária e Abastecimento serve as a guide to help milk farmers to improve milk production systems as a whole, as the activity is multifactorial by nature.